Environment and Breast Cancer - Russo, Jose.; Russo, Jose. (Springer New York : Imprint: Springer, 2011)
Breast cancer is a complex disease caused by multiple environmental and lifestyle factors interacting with genetic susceptibility across the life span. Therefore, environmental factors are of intense interest to both researchers and community members, including women with breast cancer. There is not adequate literature that addresses this issue comprehensively from epidemiological, experimental, and translational research perspective. This book is aiming to fill this gap by gathering in 11 chapters the most recognized expert in the field of breast biology and cancer with special interests in environmental issues.